A Clinical Profile of Pediatric COVID-19 Testing in the Emergency Department, Dubai, United Arab Emirates - Fatima Farid Mir; Maysa Saleh (International Journal of Pediatrics)
Background. The COVID-19 pandemic marked a health and economic crisis of massive proportions. In its early months, literature was centered on adult medical and critical care. As time progressed, international reports of COVID-19 infection in children steadily grew; however, data on disease features in the United Arab Emirates’ pediatric population was noticeably lagging. Method. The presented research was conducted at Latifa Women and Children Hospital Emergency Department to ascertain an association between a child’s presenting features and basic investigations to a subsequent positive COVID-19 test result. Data was collected via electronic medical records and statistical analysis performed with SPSS version 22.0. Results. A total of four hundred and five (405) patients were analyzed, with 32 (8%) being COVID-19 positive on initial testing in emergency department. There is a statistically significant correlation (p<0.05) between testing positive for COVID-19 infection and history of exposure to COVID-19-positive individuals; the presence of runny nose, cough, poor feeding, and abdominal pain with reassuring physical examination findings; and predominantly normal reports of basic blood investigations and chest X-ray images. Conclusion. This research demonstrates that a minority of children tested for COVID-19 in the initial wave of the pandemic tested positive. A significant proportion of COVID-19-positive pediatric patients exhibit history of exposure to COVID-19-positive individuals; the presence of runny nose, cough, poor feeding, and abdominal pain; normal physical examination; normal basic blood investigations and chest X-ray findings.